2012
DOI: 10.1007/s12603-012-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle mass abnormalities are associated with survival rates of institutionalized elderly nursing home residents

Abstract: About two thirds of nursing home patients show skeletal muscle mass abnormalities, most within the range of very low skeletal muscle mass rather than moderately low skeletal muscle mass, that are associated with shorter survival rates, compared with normal skeletal muscle mass patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
0
28
1
1
Order By: Relevance
“…Whether muscle strength or mass has a stronger effect on outcomes in elderly adults remains controversial. Muscle strength has been found to be more important than muscle mass in the Health, Aging and Body Composition study cohort, although there is evidence of the harmful effect of low muscle mass on outcomes in community‐dwelling and institutionalized elderly adults . Another study showed that lean mass loss leads to loss in muscle strength .…”
Section: Discussionmentioning
confidence: 99%
“…Whether muscle strength or mass has a stronger effect on outcomes in elderly adults remains controversial. Muscle strength has been found to be more important than muscle mass in the Health, Aging and Body Composition study cohort, although there is evidence of the harmful effect of low muscle mass on outcomes in community‐dwelling and institutionalized elderly adults . Another study showed that lean mass loss leads to loss in muscle strength .…”
Section: Discussionmentioning
confidence: 99%
“…It leads to nosocomial infections [3], postoperative complications [4][5][6][7], increased length of hospital stay [7,8], and decreased survival in nonmalignant as well as malignant populations [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the prevalence of sarcopenia was 85.4%. In Israel, the prevalence of skeletal muscle mass abnormalities in 109 nursing home residents was 67.0%; 97.8% in males and 43.8% in females [18]. In Italy, Landi et al, 2012 [19] conducted their study on 122 nursing home residents, their mean age was 84.1 ± 6.9.…”
Section: Discussionmentioning
confidence: 99%